Changes of meteorological factors and tick-borne encephalitis incidence in the Czech Republic - Daniel, M; Kríz, B; Danielová, V; Valter, J; Benes, C (Epidemiologie, mikrobiologie, imunologie, 2009)
OBJECTIVES: The primary objective was to analyze the influence of short-term meteorological changes during the vegetation period on the incidence of tick-borne encephalitis (TBE) in the 1990s, characterized by a dramatic increase in reported TBE cases in the Czech Republic and other European countries. Furthermore, the relationship between TBE incidence and meteorological conditions in the previous winter season was studied. MATERIAL AND METHODS: The TBE incidence data were acquired from the EPIDAT database of the National Institute of Public Health (NIPH). Analyzed were a total of 4637 cases reported in Bohemia (1994-2004). Meteorological data were from the database of the Czech Hydrometeorological Institute in Prague and originated from 22 meteorological stations located in high TBE incidence areas in Bohemia. RESULTS: A linear relationship was found between TBE incidence and temperature factors in all the years under study. Lagged cross-correlation analysis (with the time lag corresponding to the incubation period from the infected tick bite to the onset of TBE symptoms) revealed a close correlation between TBE incidence and weekly mean air temperature with a lag of 1 to 5 weeks. When considering the previous winter period, the closest relationship was found between TBE incidence and the previous-winter frost index, followed by the minimum air temperature. CONCLUSION: A review is presented of the effects of the currently observed climate change on TBE incidence as compared with the data reported in the 1950s. Results of parallel analyses of other factors potentially implicated in higher TBE incidence in the 1990s lead to a critical rejection of the conclusion previously drawn by some authors that the collapse of communism and subsequent dramatic socio-economic changes might have a decisive influence on TBE incidence in Central Europe. The rise in TBE cases reported in West European countries where no such political changes took place confirms the refutation.
Keywords: Humans; Česká republika; lidé; Meteorological Concepts; Encephalitis, Tick-Borne; meteorologické pojmy; klíšťová encefalitida; incidence; Incidence; Czech Republic